2015
DOI: 10.1002/cyto.a.22659
|View full text |Cite
|
Sign up to set email alerts
|

Light depolarization measurements in malaria: A new job for an old friend

Abstract: The use of flow cytometry in malaria research has increased over the last decade. Most approaches use nucleic acid stains to detect parasite DNA and RNA and require complex multi-color, multi-parameter analysis to reliably detect infected red blood cells (iRBCs). We recently described a novel and simpler approach to parasite detection based on flow cytometric measurement of scattered light depolarization caused by hemozoin (Hz), a pigment formed by parasite digestion of hemoglobin in iRBCs. Depolarization meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…Flow cytometric analysis was also performed for measurement series A and C ( Figs 3 and 4 , respectively). In these experiments two different parameters were assessed simultaneously: i) fluorescence of GFP expressing parasites 13 and ii) depolarized side scattering (DSS) properties of the hemozoin-containing red blood cells 17 18 . As an inherent advantage of flow cytometry, parasite counts can be determined in both cases directly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analysis was also performed for measurement series A and C ( Figs 3 and 4 , respectively). In these experiments two different parameters were assessed simultaneously: i) fluorescence of GFP expressing parasites 13 and ii) depolarized side scattering (DSS) properties of the hemozoin-containing red blood cells 17 18 . As an inherent advantage of flow cytometry, parasite counts can be determined in both cases directly.…”
Section: Resultsmentioning
confidence: 99%
“…The need for a universally applicable and automated method for diagnostics has motivated extensive research on malaria pigment (hemozoin), a natural biomarker of the infection. In particular, various magnetic and/or optical detection schemes targeting hemozoin have been proposed 17 18 19 20 21 .…”
mentioning
confidence: 99%
“…A number of recent studies have reported on strategies to exploit physical and/or electromagnetic features of hemozoin crystals to detect infection by malaria parasites [54,[80][81][82][83][84][85][86]. Generally, the LOD of these methods is between 1 and 30 iRBCs/ml and, therefore, not as sensitive as NAA strategies.…”
Section: Emerging Malaria Diagnosticsmentioning
confidence: 97%
“…Further, hemozoin-containing monocytes observed by microscopy may provide insight regarding the total body parasite burden, as these cells do not sequester in P. falciparum infections [49,50]. Flow cytometric devices may also contribute new approaches for malaria diagnosis with emphasis on field deployment, however, further development of instrumentation is required [51][52][53][54][55]; limitations of speciesspecific detection must be acknowledged for flow cytometry.…”
Section: Microscopy and Cytometrymentioning
confidence: 98%
“…An LOD can be obtained from serially diluted cultures or samples ( 3 ). In rodent models, detection of Hz tends to be much easier ( 4 ). Moreover, in Plasmodium falciparum infections, only immature forms have been observed, with little or no detectable Hz ( 5 ).…”
mentioning
confidence: 99%